Professores bacharéis sem formação pedagógica formal e “bem-sucedidos” na docência da educação profissional - Fogaça, Márcia Rosane Juppen (Universidade do Vale do Rio dos Sinos, 2017)
This dissertation’s general objective is to analyze how bachelor professors who do not acquired formal pedagogical education are considered “successful” in their Professional education activities. Its specific objectives are as follows: to know was the entry process of the bachelor who lacks of formal pedagogical education into the Professional education field; to analyze how its self identit as a professor has been built; to discuss about which competencies and knowledge are used by the bachelor when teaching, who despite lacking of formal pedagogical education is considered a “successful” professor through examining how these competencies and knowledge are expressed during his/hers pedagogical practice. The dissertation problem that guided this study was how bachelor professor who lack of formal pedagogical training are considered “successful” in their professional education activities? Qualitative methodology was applied through recorded semi-structured interviews that were transcribed afterward its completion. The A partner company of the “S System” based in Porto Alegre was the research ground field for the interviews that counted with seven full-time professors that did not underwent formal pedagogical training but had been teaching for over three years by the time when interviewed. In order to provide theoretical support for the research, a bibliographical review of previously published papers regarding teaching skills and competencies was performed and it was also carried out a brief analysis of Brazils National Guidelines and Bases ofor Education Act, 1996 “Lei de Diretrizes e Bases da Educação Nacional de 1996”, which states about professional training for graduates aiming a career in basic education. The main authors who gave theoretical support to the study are the following: Cunha, Gauthier, Perrenoud, Pimenta, and Tardif. The analysis of the research material made it possible to affirm that the pedagogical practice of the bachelors teacher with lack of formal pedagogical training is based on his/hers experiences during his/hers formation, based on the memories of his good and bad teachers. The practices of these teachers change throughout their experiences by developing the necessary teaching knowledge for the activities. In addition, even being recognized as professors, interviewees emphasized the need of formal pedagogical training to develop pedagogical knowledge, which are also necessary for the Professional Education teacher.
Keywords: Professor bacharel; Saberes pedagógicos; Saberes pedagógicos; Competências docentes; Educação profissional; Professor bachelor; Pedagogical knowledge; Teaching skills; Professional education; ACCNPQ::Ciências Humanas::Educação